2019
DOI: 10.1093/dote/doz092.128
|View full text |Cite
|
Sign up to set email alerts
|

O128 TGF-Beta1 and TGF-Beta2 Mediated Epithelial-Mesenchymal Transition in Esophageal Adenocarcinoma Cells

Abstract: Aim he esophageal adenocarcinoma (EAC) is characterized by an early lymphogenic dissemination and a poor prognosis. The tumor biology and the impact of autocrine, paracrine and endocrine mediators are involved in these mechanisms. For dissemination, the tumor cells need to escape the solid tumor and invade into new target structures. This mechanism is described as epitheliale-mesenchymal transition (EMT), which could be initiated by TGF-beta M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our in vitro experiments indicated that CASC18 influenced TGFB2 expression and secretion, and affected CAL27 cell migration and invasion. Consistent with previous studies (Thieme 2020 ; Jiang et al 2021 ), EMT was inhibited with the attenuation of TGFB2 expression in CASC8-knockdown CAL27 cells. These data suggested that CASC18 regulated cell mobility via TGFB2-mediated EMT in TSCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our in vitro experiments indicated that CASC18 influenced TGFB2 expression and secretion, and affected CAL27 cell migration and invasion. Consistent with previous studies (Thieme 2020 ; Jiang et al 2021 ), EMT was inhibited with the attenuation of TGFB2 expression in CASC8-knockdown CAL27 cells. These data suggested that CASC18 regulated cell mobility via TGFB2-mediated EMT in TSCC cells.…”
Section: Discussionsupporting
confidence: 92%